Prevalence of internal and external parasites and their related diseases, during the rainy season: Evaluation for breed selection in a semi-arid wildlife zone - Ndlovu, Lethokuhle Joyce; Mugoti, Alban; Munengwa, Anderson; Moyo, Sizo; Matshisela, Anele; Mgumba, Chiedza La-linda (Syiah Kuala University, 2024)
Experimental research was done in Bubi district, a semi-arid region to find the prevalence of parasites and their related diseases during the rainy season. The research was done in order to identify the prevalence of both internal and external parasites of cattle kept in a wildlife zone and identify age and breed influence on hardiness. In a total population of 320 cattle, 36 cattle were sampled, considering the age and breed. Brahman, Angus, and Beef Master were used, at varying stages of growth namely calves, weaners, and cows and bulls. Veterinary assistance was sort in the identification of parasites, although literature was also used in the process. A high prevalence of external parasites was found in four identified hard ticks; the Rhipicephalus (boophilus) decloratus with an average of 27.44, Rhipicephalus appendiculatus (10.50), A.variegatum spp (0.83) and Hyalomma (0.44). Internal parasites were identified from the following species; the Fasciola spp with an average of (1.89), Fasciola eggs (1.28), Trematode eggs (2.81), Strongyle eggs (2.50), and the Ascaris lumbricoides (0.14). The blood parasite found was Anaplasma spp (1.11 bacteria per ml). Weaners were more susceptible to parasitism. Beef master was the most resilient breed against parasites. Brahman and Angus had a high level of disease resistance due to their minimum mortality recorded. Both internal and external parasitic levels were major health threats although no relationship between wildlife-livestock disease interactions was found. Weaners require more attention in parasitic treatment since they were the most susceptible.